Cloning and characterization of drought stress-induced NAC transcription factors from Brassica juncea and Sinapis alba - Phukan, Dharitree; Singh P, Bhupendra; Ravi1, Indu; Mithra, Amitha S. V.; Yadava, Devendra K.; Chinnusamy, Viswanathan; Mohapatra, Trilochan (The Indian Journal of Genetics and Plant Breeding, 2016)
The plant specific NAC [for NAM (no apical meristem), ATAF, CUC (cup-shaped cotyledon)] TFs are one of the largest plant TF families that play important roles in plant development and stress tolerance. Suppression subtractive hybridization (SSH) analysis with using drought stressed plants of S. alba lead to the identification of several stress responsive ESTs. Two of them homologous to Arabidopsis NAC14 and NAC19 were selected for cloning of full length CDS and expression analysis in Brassicaand related species with contrasting drought tolerance. NAC14 and NAC19 genes were cloned from drought tolerant Sinapis alba and Brassica juncea cvs. RGN73 and Varuna, and drought sensitive B. juncea cvs. RLM619, BEC144 and BioYSR. Sequencing of genomic region coding for these NACs revealed that both NAC14 and NAC19 contain 3 exons and 2 introns each. In silico analysis of protein structure led to development of 3D models of these stress responsive NAC TFs. Although both proteins have 7 strands of Î² sheets, the NAC14 had 5 Î² sheets of type A and 2 Î² sheets of type B, while NAC14 have all 7 Î² sheets of type A. These proteins also differed in helix content, Î² turns and g turns. This suggest their functional diversity under abiotic stresses. Real-time RT-PCR expression analysis revealed that both the genes were up-regulated under drought stress in the leaves of B. juncea genotypes Varuna and BioYSR. In addition, NAC14 was up-regulated in the leaves of RLM619, while NAC19 was up-regulated in the leaves of S. alba and BEC144 under drought stress as compared to control conditions. Interestingly, drought stress did not up-regulate these genes in RGN73. This study revealed genotypic variation in the drought regulation of NAC TFs in B. juncea and S. alba.